PENGARUH KARAKTERISTIK PERUSAHAAN TERHADAP UPAYA PENGHINDARAN PAJAK (STUDI PADA PERUSAHAAN MANUFAKTUR YANG TERGABUNG DALAM INDEKS SAHAM SYARIAH INDONESIA TAHUN 2012-2015) - Ulwan Hawari (Jurnal Ilmiah Mahasiswa FEB, 2017)
This research aims to examine and analyze the influence of firm characteristic on tax  avoidance.  Firm  characteristic  is  represented  by size,  leverage,  capital intensity,  inventory  intensity.  Tax  avoidance in this  research  is  measured  by Effective Tax Rate (ETR) that is ratio of total income tax expense before total pre- tax accounting income. The sample that used in this study are secondary data of manufactured companies  on  Indeks  Saham  Syariah  Indonesia  (ISSI)  on  the Indonesia Stock Exchange (BEI) for the period of 2012-2015. Sample selection uses  purposive  sampling  technique  and  hypothesis  testing uses  data  panel multiple  regression  analysis  with  EViews  9.  The result  showed  that  capital intensity and inventory intensity have a negative effect and significant in tax avoidance. However, size and leverage did not influence the tax avoidance. Keywords: Tax avoidance, size, leverage, capital intensity, inventory intensity